Continuous reuse of polyamide 12 in powder bed fusion - Aleksander Kubeczek; Michał Olejarczyk; Piotr Gruber; Arkadiusz J. Antończak (Scientific Reports)
Abstract The thermal degradation of polymers in powder bed fusion (PBF) is one of the major issues preventing wider adoption of this technology at the production scale. Although standard PBF allows for elastic production of complex parts in a single-step manufacturing process, it is materially inefficient. This is because only approximately 10% of the material is used to develop parts, while the majority of semicrystalline polyamide 12 (PA12) remain unused. The recovered powder cannot be directly reused in subsequent processes because it remains at high temperatures, above the glass transition and below the melting point for a long time during printing. In this work, we present a novel way to process PA12 at room temperature without exposure to a thermal agent. Dual beam laser sintering (DBLS) uses a double laser system that effectively compensates for the temperature in the melting zone and prevents material shrinkage. To demonstrate the effectiveness of the DBLS method, the material was kept in a closed loop. Specimens from each iteration of the process (n = 4) were analyzed. No significant changes were observed in the chemical properties (molecular weight and melt viscosity, assessed via gel permeation chromatography (GPC) and melt flow index (MFI) analysis), rheological properties (flowability and size distribution) nor in the particle shape of the powder samples. Mechanical properties of the built specimens, when compared with the initial values, proved to be satisfactory.